2010
DOI: 10.1002/mus.21605
|View full text |Cite
|
Sign up to set email alerts
|

FYN‐dependent muscle–immune interaction after sciatic nerve injury

Abstract: Denervation of skeletal muscles results in loss of muscle mass and contractile force. Recent evidence suggests that local immune system activation plays a key role in these processes, but the mechanisms underlying muscle-immune system cross-talk are not understood. The purpose of this study was to address the mechanisms by which muscle responds to denervation and to elucidate the specific role played by FYN in local immune system activation. We studied initial events taking place in the gastrocnemius of wild-t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…We have already known that, In the central nervous system (CNS), Fyn controls switches in a variety of signal transduction pathways governing cell growth, division, differentiation, and survival [33] by assembling a unique platform, lipid rafts [34]. It has also been noted that the principle of Fyn activation appears to be realized by its affinity with receptors for growth factors, especially, IGF-1R, and the specialized cellular communication within the lipid rafts.…”
Section: Discussionmentioning
confidence: 99%
“…We have already known that, In the central nervous system (CNS), Fyn controls switches in a variety of signal transduction pathways governing cell growth, division, differentiation, and survival [33] by assembling a unique platform, lipid rafts [34]. It has also been noted that the principle of Fyn activation appears to be realized by its affinity with receptors for growth factors, especially, IGF-1R, and the specialized cellular communication within the lipid rafts.…”
Section: Discussionmentioning
confidence: 99%
“…Inflammasome. Denervation induces an early and transient increase in muscle levels of TNF-α and IL-1β (20), which are products of inflammasome activation (21). Because activation of the nuclear factor kappa-light-chain-enhancer of activated B cells (NF-κB), a transcription factor, induces muscle atrophy (1), we decided to evaluate levels of the phosphorylated form of p65 (P-p65), an active subunit of NF-κB (22).…”
Section: Denervation Of Fast Skeletal Muscles Induces Activation Of Thementioning
confidence: 99%
“…As reported, growth factors usually result in a quick and adaptive response, and mediate changes allowing an animal to effec-tively face mobilization [3]- [7]. Coincidently, we have characterized that Fyn, one of Src kinases, represented the predominant signaling in VEGFR-2 activation and VEGFR-1 shuttling between membrane and ER, which initiated stereotypic inflammation and muscle-T cell interaction during muscle denervation [8]- [10]. Therefore, it was proposed that subcellular communication might form a viable link to functional muscular stabilization.…”
Section: Introductionmentioning
confidence: 84%
“…Previously, we reported that timely Fyn activation triggered a particular microenvironment in the denervated gastrocnemius, which evoked early muscular inflammation and later local immunological changes via specific subcellular communication [8] [9]. Herein, gastrocnemius mobilization was established and it was observed that extracellular calcium level was elevated, which happened rapidly and sustained within one week of operation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation